Pain acceptance and illness intrusiveness in low-back pain: A longitudinal study - Simoncsics, Eszter; Konkolý Thege, Barna; Stauder, Adrienne (Frontiers in Psychiatry, 2022)
AAbstract BACKGROUND: In chronic pain syndromes, acceptance of pain may be a better approach than pain control. So far, little data have been available on how pain and its acceptance affect illness intrusiveness among patients with low-back pain (LBP). OBJECTIVE: The present longitudinal study evaluates the impact of pain acceptance on illness intrusiveness in patients with LBP. METHODS: Study participants were asked to complete the following questionnaires during their visit (T1) at one of four diverse rheumatologic outpatient clinics, and then two to three months later (T2) via phone or online: Chronic Pain Acceptance Questionnaire (CPAQ), Illness Intrusiveness Rating Scale (IIRS), Roland Morris Disability Questionnaire (RMDQ), Patient Health Questionnaire Depression subscale (PHQ9), and socioeconomic data. RESULTS: One hundred and twenty-seven individuals completed the questionnaires at baseline (31 having acute, 15 subacute and 81 chronic low back pain) and 97 at follow-up. Illness intrusiveness was negatively correlated with chronic pain acceptance both at T1 (r=-0.39) and T2 (r=-0.44). Illness intrusiveness scores have not changed significantly from T1 (M=28,.59 SD=13,.08) to T2 (M=28,.24, SD=15,.76). In a multiple regression model - including pain intensity, functional status, pain acceptance, depression severity, age, sex and educational level - the independent predictors of follow-up illness intrusiveness scores were lower pain acceptance and higher depression scores. CONCLUSIONS: In our study, patients with acute, subacute and chronic low back pain reported similar levels of illness intrusiveness. In addition, illness intrusiveness scores have not changed significantly during the 2-month follow-up period and pain acceptance proved to be a significant independent predictor of illness intrusiveness among patients with chronic low-back pain.